"You probably can't feel as safe as normal women": Hispanic women's reactions to breast density notification. Issue 12 (15th February 2019) - Pacsi‐Sepulveda, Alsacia L.; Shelton, Rachel C.; Rodriguez, Carmen B.; Coq, Arielle T.; Tehranifar, Parisa
Abstract : Background: Patient advocacy has led to state‐level legislative mandates for the release of personal mammographic breast density information to women undergoing screening mammography. More research is needed to understand the impact of this information on women's perceptions and mammography screening behavior. Methods: Semistructured interviews were conducted in English and Spanish with 24 self‐identified Hispanic women who had undergone at least 1 mammogram since breast density notification was enacted in New York State. The women ranged in age from 43 to 63 years. Women were asked about their understanding and perceptions of the communication of New York State‐mandated breast density information, and any actions they have taken or would take in response to this information. A content analysis of the qualitative data from the translated and transcribed interviews was conducted. Results: The majority of participants had no prior knowledge of breast density and expressed confusion and apprehension regarding the meaning of dense breasts when presented with the notification information. Many participants understood having dense breasts to be a serious and abnormal condition, and reported feelings of worry and vulnerability. Participants mostly expressed a strong interest in learning about breast density and obtaining additional and more frequent breast cancer screening tests. These behavioral intentions were consistent with participants' overall favorable view of breast cancer screening and a belief that their faith, as well as regular screening, can help to protect them from breast cancer morbidity and mortality. Conclusions: Hispanic women conveyed proactive breast cancer screening intentions in response to breast density notification, despite inadequate comprehension of this information and negative emotional responses. Abstract : State‐level legislation mandates written notification to women with dense breasts regarding their lower rates of mammographic detection and higher risk of breast cancer. The current study examines Hispanic women's understanding and reactions to breast density notification and their actual and intended health care behaviors.